Explaining the Applied Postmodernism - Marques Vianna Querino, Gustavo (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2024)
The Enlightenment project is considered obsolete due to a distrust in reason and the humanity's capacity to comprehend reality and nature. The crisis of the Marxist project led to the need for new strategies and explanations for the continued success of industrial society, resulting in a new intellectual school and a critical method to address such issues. This article explores the origins of the philosophical foundations of postmodernism according to Stephen Hicks and the conjunctural changes in identity according to Stuart Hall. Furthermore, it presents the relationship between these theses and the origin of "applied postmodernism," a term coined by Pluckrose and Lindsay to describe the practical implementation of postmodern ideas.